Meta-analysis reveals ammonia-oxidizing bacteria respond more strongly to nitrogen addition than ammonia-oxidizing archaea. (August 2016) - Carey, Chelsea J.; Dove, Nicholas C.; Beman, J. Michael; Hart, Stephen C.; Aronson, Emma L.
Abstract: Shifts in microbial communities driven by anthropogenic nitrogen (N) addition have broad-scale ecological consequences. However, responses of microbial groups to exogenous N supply vary considerably across studies, hindering efforts to predict community changes. We used meta-analytical techniques to explore how amoA gene abundances of ammonia-oxidizing archaea (AOA) and bacteria (AOB) respond to N addition, and found that N addition increased AOA and AOB abundances by an average of 27% and 326%, respectively. Responses of AOB varied by study type, ecosystem, fertilizer type, and soil pH, and were strongest in unmanaged wildland soils and soils fertilized with inorganic N sources. Increases in nitrification potential with N addition significantly correlated with only AOB. Our analyses suggest that elevated N supply enhances soil nitrification potential by increasing AOB populations, and that this effect may be most pronounced in unmanaged wildland soils. Highlights: We quantitatively synthesized soil ammonia oxidizer response to nitrogen addition. Nitrogen addition stimulated both AOA and AOB amoA gene abundances. AOB abundances increased more than AOA in response to nitrogen addition. AOB showed a significant positive relationship with nitrification potential.